Metadherin: A Therapeutic Target in Multiple Cancers - Dhiman, Gourav; Srivastava, Neha; Goyal, Mehendi; Rakha, Emad; Lothion-Roy, Jennifer; Mongan, Nigel P.; Miftakhova, Regina R.; Khaiboullina, Svetlana F.; Rizvanov, Albert A.; Baranwal, Manoj (Frontiers in Oncology, 2019)
Altered expression of many genes and proteins is essential for cancer development and progression. Recently, the affected expression of metadherin (MTDH), also known as AEG-1 (Astrocyte Elevated Gene 1) and Lyric, has been implicated in various aspects of cancer progression and metastasis. Elevated expression of MTDH/AEG-1 has been reported in many cancers including breast, prostate, liver and esophogeal cancers, whereas its expression is low or absent in non-malignant tissues. These expression studies suggest that MTDH may represent a potential tumor associated antigen. MTDH also regulates multiple signalling pathways including PI3K/Akt, NF-κB, Wnt/β-catenin and MAPK which cooperate to promote the tumorigenic and metastatic potential of transformed cells. Several microRNA have also been found to be associated with the increased MTDH expression in different cancers. Increased MTDH levels were linked to the tumor chemoresistance making it an attractive novel therapeutic target. In this review, we summarize data on MTDH function in various cancers.